Eksistensi Perempuan dalam Novel "Lebih Senyap Dari Bisikan" Karya Andina Dwifatma: Feminisme Eksistensial Simone de Beauvoir - Ridwan, Ridwan; Nensilianti, Nensilianti; Hamid, Reski Aulia (Nuances of Indonesian Language, 2024)
This research aims to find and describe the form of gender injustice and the form of women's resistance in the novel Lebih Senyap dari Bisikan by using Simone de Beauvior's existential feminism theory approach. The data source in this research is taken from the novel Lebih Senyap dari Bisikan by Andina dwifatma. Data collection in this study used reading and note-taking techniques. The results of this study show the existence of gender injustice in the form of discrimination, biological conditions, and a form of resistance in the form of rejection of women as others as well as additional workloads on women to find and show the existence of the female characters from this novel.